Implementation of Direct Fuel Cash Transfer: Policy Recycling (Case Study in Kendari City) - Suaib, Eka; Tarifu, La; ., Aminuddin; ., Liwaul; Ningsih, Anita (KnE Social Sciences, 2023)
The Fuel Oil Direct Cash Transfer Program (BLT-BBM) is a government assistance program that give cash or various other services. This program is one of the efforts to overcome poverty in many countries that have been implemented in over 65 countries since the 2000s. The purpose of this study was to understand the recycling of BLT-BBM policies. This research was qualitative, with information gathered from program implementers from the Social Service, PT. Post, social worker escort workforce. The study was conducted in Kendari City. The results showed a BLT BBM in 2022, and there were similarities in the BLT program in 2003, 2005, 2008, and 2020. The implementors of the program recycle from the previous policy by modifying it a little at a time. Modifications are the regulatory basis, beneficiaries, assistance amount, payment period, nominal payment, and data verification. The theoretical implication of this study was that public policy continues to create a complex system because policy implementors in solving problems are not willing to face the real problem, work perfunctorily, and only polish it little at a time from the existing policy. Keywords: Cash Transfer, Recycling Policy, Incremental Theory, BLT Fuel